Pengamanan Pesan Menggunakan Algoritma One Time Pad dengan Linear Congruential Generator sebagai Pembangkit Kunci - Maghfiroh, Jamilatul; Turmudi, Turmudi; Susanti, Elly (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2023)
Cryptography is one method that can be used to secure a message by hiding the original text. This study uses the One Time Pad (OTP) algorithm to secure a message and the Linear Congruential Generator (LCG) algorithm as a key generator. The purpose of this study is to describe the key generation process using the LCG algorithm, the encryption and decryption process of messages using the OTP algorithm. The process of encrypting and decrypting messages using the OTP algorithm requires a key as long as the original message and must be random. Therefore, a random number generation process is carried out using the LCG algorithm before encoding the message. The results of this study are the LCG algorithm is able to build dynamic keys with the condition that the length of the period must be greater than or equal to the length of the plaintext. The process of encoding messages using the OTP algorithm has a high level of security because the number of characters used is more and the process of sending messages is easier. The resulting ciphertext is a very random and unreadable message that is difficult to decipher.